A Comprehensive Review on Ethno-phytopharmacological Profile of Medicinal Plant Pedalium murex - Mohandass, Vasanth; Sankaramourthy, Divya; Kanagavel, Yogesh; Padinakara, Anupama Cherayi; Krishnasamy, Kaveri (Asian Journal of Biological and Life Sciences, 2025)
In the modern era, drug discovery and development from phytocompounds have hugely increased as medicinal plants are known for their inherent therapeutic nature against various ailments. Also, the practice of the phytotherapeutic approach has increased significantly as they are more effective with minimal side effects. The medicinal plant Pedalium murex is an herbaceous plant that belongs to the family Pedaliaceae and has numerous medicinal properties. The current review briefs and focuses on the phytochemical and pharmacological characteristics of Pedalium murex and reviews previous research reports. The only means of dealing with the adverse effects of synthetic medications is to rely on phytomedicines. Through toxicity testing, adverse effects associated with the use of phytomedicines can be detected, which enables the prevention of possible hazardous side effects. Pedalium murex has the potential to be used for the development of novel drugs. The plant is chiefly known for its efficacy in treating various complications, namely urinary disorders such as Ardorurinae, Dysuria, and Spermatorrhoea; diabetes; and cancer, and as an aphrodisiac, antioxidant, and nootropic. This review gives an eagle’s view on a pharmacological activity from several parts of the herbs with both therapeutic and environmental advantages.
Keywords: Anti-cancer; Anti-urolithiatic; Antioxidant; Pedalium murex; Toxicity